2011
DOI: 10.1519/jsc.0b013e31820238aa
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme/Vitamin D Receptor Gene Polymorphisms and Bioelectrical Impedance Analysis in Predicting Athletic Performances of Italian Young Soccer Players

Abstract: We evaluated the association between 2 genetic polymorphisms known to be involved in fitness and performance, and anthropometric features, body composition, and athletic performances in young male soccer players with the goal of identifying genetic profiles that can be used to achieve maximal results from training. One hundred twenty-five medium-high-level male soccer players were genotyped for angiotensin-converting enzyme (ACE) I/D, and vitamin D receptor (VDR) FokI gene polymorphisms and scored for anthropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Hopkinson et al [245] have found that both patients with chronic obstructive pulmonary disease (n ¼ 107) and control subjects (n ¼ 104) who were homozygous for the C allele of the FokI polymorphism had less quadriceps strength than did those with TC or TT genotype. Micheli et al [246] have observed significant differences in VDR FokI genotype frequencies between medium-high-level male soccer players (n ¼ 125) and sedentary controls. Homozygous TT genotype of the VDR gene was significantly more represented in young soccer players than in a matched sedentary population.…”
Section: Vdr Rs10735810 T Allelementioning
confidence: 98%
“…Hopkinson et al [245] have found that both patients with chronic obstructive pulmonary disease (n ¼ 107) and control subjects (n ¼ 104) who were homozygous for the C allele of the FokI polymorphism had less quadriceps strength than did those with TC or TT genotype. Micheli et al [246] have observed significant differences in VDR FokI genotype frequencies between medium-high-level male soccer players (n ¼ 125) and sedentary controls. Homozygous TT genotype of the VDR gene was significantly more represented in young soccer players than in a matched sedentary population.…”
Section: Vdr Rs10735810 T Allelementioning
confidence: 98%
“…Furthermore, VDR expression levels reduce with age and VDR genotypes have been associated with fat-free mass and strength in elderly individuals (40). Few studies have specifically examined the association between VDR polymorphisms and exercise training, and to the best of our knowledge only one study has analyzed the association between VDR polymorphisms and football performance (23). A previous study (41) observed a significant increase in the expression levels of VDR at day 7 of muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study aimed to assess vitamin D levels in professional American football players and to evaluate the association between vitamin D levels and ethnic group, fracture history, and the ability to obtain a contract position (19 (20,21). Thus, the performance of professional football players and their susceptibility to injury may be influenced by genetic factors (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Some other gene polymorphisms have been associated with sport performance, although results are still preliminary or controversial. These include polymorphisms in the alpha2a-adrenoceptor gene (ADRA2A) 179 , bradykinin beta 2 receptor (BDKRB2) and endothelial nitric oxide synthase 3 (NOS3) genes 180 , vitamin D receptor gene 181,182 , and AT-Pase, Ca2+ transporting, cardiac muscle, slow twitch 2 (ATP2A2), the NUAK family, SNF1-like kinase, 1 (NUAK1), and the protein phosphatase 1, catalytic subunit, gamma isoform (PPP1CC) genes 183 .…”
Section: Other Gene Related To Fitness Phenotypementioning
confidence: 99%